Does Prewriting Planning Positively Impact English L2 Students’ Integrated Writing Performance? - Uludag, Pakize; McDonough, Kim; Payant, Caroline (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2021)
This study compared English L2 writers’ (N = 111) performance on an integrated writing task from the Canadian Academic English Language (CAEL) Assessment under three prewriting planning conditions: required self-timed planning required fixed time planning, and suggested (i.e., optional) planning. The participants’ integrated essays were scored according to the CAEL writing bands by raters at Paragon Testing Inc. The effect of planning condition on the participants' planning time, writing time, and integrated writing scores were analyzed using MANOVA. The student interviews were analyzed using thematic content analysis. The results indicated that planning time was the only variable impacted by planning condition, with students in the required self-timed planning condition taking more time to plan before beginning to write. Students’ perceptions about prewriting planning are discussed in terms of implications for the teaching and assessment of L2 integrated writing.